Combinatorial Pharmacogenetic Interactions of Bucindolol and β1, α2C Adrenergic Receptor Polymorphisms - O'Connor, Christopher M.; Fiuzat, Mona; Carson, Peter E.; Anand, Inder S.; Plehn, Jonathan F.; Gottlieb, Stephen S.; Silver, Marc A.; Lindenfeld, JoAnn; Miller, Alan B.; White, Michel; Walsh, Ryan; Nelson, Penny; et al. (PLOS ONE, 2012)
Background Pharmacogenetics involves complex interactions of gene products affecting pharmacodynamics and pharmacokinetics, but there is little information on the interaction of multiple genetic modifiers of drug response. Bucindolol is a β-blocker/sympatholytic agent whose efficacy is modulated by polymorphisms in the primary target (β1 adrenergic receptor [AR] Arg389 Gly on cardiac myocytes) and a secondary target modifier (α2C AR Ins [wild-type (Wt)] 322–325 deletion [Del] on cardiac adrenergic neurons). The major allele homozygotes and minor allele carriers of each polymorphism are respectively associated with efficacy enhancement and loss, creating the possibility for genotype combination interactions that can be measured by clinical trial methodology. Methodology In a 1,040 patient substudy of a bucindolol vs. placebo heart failure clinical trial, we tested the hypothesis that combinations of β1389 and α2C322–325 polymorphisms are additive for both efficacy enhancement and loss. Additionally, norepinephrine (NE) affinity for β1389 AR variants was measured in human explanted left ventricles. Principal Findings The combination of β1389 Arg+α2C322–325 Wt major allele homozygotes (47% of the trial population) was non-additive for efficacy enhancement across six clinical endpoints, with an average efficacy increase of 1.70-fold vs. 2.32-fold in β1389 Arg homozygotes+α2C322–325 Del minor allele carriers. In contrast, the minor allele carrier combination (13% subset) exhibited additive efficacy loss. These disparate effects are likely due to the higher proportion (42% vs. 8.7%, P = 0.009) of high-affinity NE binding sites in β1389 Arg vs. Gly ARs, which converts α2CDel minor allele-associated NE lowering from a therapeutic liability to a benefit. Conclusions On combination, the two sets of AR polymorphisms 1) influenced bucindolol efficacy seemingly unpredictably but consistent with their pharmacologic interactions, and 2) identified subpopulations with enhanced (β1389 Arg homozygotes), intermediate (β1389 Gly carriers+α2C322–325 Wt homozygotes), and no (β1389 Gly carriers+α2C322–325 Del carriers) efficacy.